Student Entrepreneurship and Research Commercialization at Universities in Azerbaijan, Colombia, Egypt, India, Poland, and Portugal - Pańkowska, Małgorzata; Bayramowa, Gulshen; Cesar Augusto Diaz Moya,; Fakhreldin, Hadia; Younis, Zeinab; Nanda, Neena; Sara Brito Filipe,; Felox, Marta (European Journal of Sustainable Development, 2025)
This study examines student entrepreneurship and research commercialization practices across six countries: Azerbaijan, Colombia, Egypt, India, Poland, and Portugal. Drawing on a comprehensive literature review and original student survey data, the study investigates how entrepreneurial intention, student capabilities, and external factors—such as institutional support, funding access, and mentorship—affect the commercialization of university-based research. Structural Equation Modelling (SEM) was deployed to analyze relationships among four key latent variables: Student Capabilities (SCAP), External Circumstances Influencing Research (ECIR), Entrepreneurial Intention (EN), and Research Commercialization (RC). The findings reveal significant cross-national variation. While entrepreneurial intention positively correlates with commercialization in some contexts, such as Portugal and Poland, this relationship is weaker or absent in others, including India and Azerbaijan. This suggests that individual motivation alone is inadequate without institutional alignment and external support structures. Moreover, student cognizance of available commercialization pathways and support services was varying, indicating a need for clearer institutional communication and engagement policies. The study contributes to the literature by offering a multi-country comparative framework for analyzing student-driven innovation. It also underscores the importance of culturally responsive policies and targeted interventions that address both individual-level capabilities and system-level barriers. Based on the findings, the article recommends integrated strategies for universities and policymakers, including improved mentorship programs, streamlined commercialization processes, and enhanced visibility of support resources. These steps are essential for fostering inclusive and effective entrepreneurial ecosystems in higher education institutions across diverse socio-economic contexts. Keywords: student entrepreneurship, research commercialization, student competencies, social capital, mentorship, Structural Equation Modeling